GLEAM: The GaLactic and Extragalactic All-Sky MWA Survey. (22nd June 2015) - Wayth, R. B.; Lenc, E.; Bell, M. E.; Callingham, J. R.; Dwarakanath, K. S.; Franzen, T. M. O.; For, B.-Q.; Gaensler, B.; Hancock, P.; Hindson, L.; Hurley-Walker, N.; Jackson, C. A.; et al.
Abstract: GLEAM, the GaLactic and Extragalactic All-sky MWA survey, is a survey of the entire radio sky south of declination + 25° at frequencies between 72 and 231 MHz, made with the MWA using a drift scan method that makes efficient use of the MWA's very large field-of-view. We present the observation details, imaging strategies, and theoretical sensitivity for GLEAM. The survey ran for two years, the first year using 40-kHz frequency resolution and 0.5-s time resolution; the second year using 10-kHz frequency resolution and 2 s time resolution. The resulting image resolution and sensitivity depends on observing frequency, sky pointing, and image weighting scheme. At 154 MHz, the image resolution is approximately 2.5 × 2.2/cos (δ + 26.7°) arcmin with sensitivity to structures up to ~ 10° in angular size. We provide tables to calculate the expected thermal noise for GLEAM mosaics depending on pointing and frequency and discuss limitations to achieving theoretical noise in Stokes I images. We discuss challenges, and their solutions, that arise for GLEAM including ionospheric effects on source positions and linearly polarised emission, and the instrumental polarisation effects inherent to the MWA's primary beam.